1997
DOI: 10.1006/viro.1997.8748
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Reverse Transcriptase of a Human Immunodeficiency Virus Type 1 Group O Isolate

Abstract: The catalytic properties and sensitivity to different inhibitors have been determined for the reverse transcriptase (RT) of group O human immunodeficiency virus type 1 (HIV-1). The RT-coding region was cloned from a new HIV-1 group O isolate from Spain, expressed in Escherichia coli, and purified by affinity chromatography. This new RT showed 79% amino acid sequence identity with the corresponding enzyme of group M subtype B strain BH10. The two enzymes showed very similar kinetics of RNA-dependent DNA polymer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
57
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 52 publications
(57 citation statements)
references
References 52 publications
0
57
0
Order By: Relevance
“…21). In a preliminary study, we reported on the expression and characterization of an HIV-1 group O RT (ESP1 isolate) (22). ESP1 RT shares 79% amino acid sequence identity with the RT of group M:subtype B strain BH10.…”
Section: /Ebi Data Bank With Accession Number(s) Af068947 and Af378083mentioning
confidence: 99%
See 4 more Smart Citations
“…21). In a preliminary study, we reported on the expression and characterization of an HIV-1 group O RT (ESP1 isolate) (22). ESP1 RT shares 79% amino acid sequence identity with the RT of group M:subtype B strain BH10.…”
Section: /Ebi Data Bank With Accession Number(s) Af068947 and Af378083mentioning
confidence: 99%
“…nevirapine, delavirdine, and the TIBO derivative R82913) (23). The presence of Cys-181 in the group O RT-coding region, instead of the Tyr-181 found in sensitive group M:subtype B (M:B) strains, appears to confer NNRTI resistance (22,23). Unfortunately, detailed studies on the enzymatic activity of HIV-1 ESP1 and related M:B/O RT chimeras was hampered by the poor level of HIV-1 ESP1 group O subunit expression, reconstitution, and purification.…”
Section: /Ebi Data Bank With Accession Number(s) Af068947 and Af378083mentioning
confidence: 99%
See 3 more Smart Citations